Pengaruh Penggunaan Fungi Mikoriza Arbuskula terhadap Produksi dan Karakteristik Fisiologis Lamtoro Mini (Desmanthus virgatus) pada Tanah Salin: The Effect of The Use of Arbuscular Mycorrhizal Fungi on The Production and Physiological Characteristics of Lamtoro Mini (Desmanthus virgatus) on Saline Soil (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
This study aims to evaluate the quality of Arbuscular Mycorrhizal Fungi (AMF) inoculum produced using various nutrient fortification methods for Desmanthus virgatus plants in helping to cope with salinity stress. This study was conducted at the Agrostology Laboratory of IPB University with a Completely Randomized Design (CRD) Factorial Pattern 5 x 3 with 8 replications. Factor A was types of AMF, namely AMF without administration (JM0), commercial/superior AMF (JMU), AMF fortified with AB Mix 1000 ppm (JM1), AMF fortified with AB Mix 2000 ppm (JM2), and AMF fortified with AB Mix 3000 ppm (JM3). Factor B was levels of soil salinity, namely control soil (JT0), medium saline soil (JT1), and high saline soil (JT2). Each plant was given 20 g of AMF, compost, and NPK fertilizers. Both plants without AMF and with AMF were given different doses of fertilizer, namely 100% dose and 50% dose. The results showed that inoculation of JMU, JM1, JM2 and JM3 had the same AMF colonization consistency in JT0, JT1 and JT2. AMF inoculation of JMU, JM1, JM2, and JM3 effectively increased (p